Efficacy of eculizumab in paroxysmal nocturnal hemoglobinuria patients with or without aplastic anemia: prospective study of a Korean PNH cohort - Choi, Chul Won; Jang, Jun Ho; Kim, Jin Seok; Jo, Deog-Yeon; Lee, Je-Hwan; Kim, Sung-Hyun; Kim, Yeo-Kyeoung; Won, Jong-Ho; Chung, Joo Seop; Kim, Hawk; Lee, Jae Hoon; Kim, Min Kyoung; et al. (Blood research, 2017)
Patients with paroxysmal nocturnal hemoglobinuria (PNH) often have concurrent aplastic anemia (AA). This study aimed to determine whether eculizumab-treated patients show clinical benefit regardless of concurrent AA. We analyzed 46 PNH patients ≥18 years of age who were diagnosed by flow cytometry and treated with eculizumab for more than 6 months in the prospective Korean PNH registry. Patients were categorized into two groups: PNH patients with concurrent AA (PNH/AA, N=27) and without AA (classic PNH, N=19). Biochemical indicators of intravascular hemolysis, hematological laboratory values, transfusion requirement, and PNH-associated complications were assessed at baseline and every 6 months after initiation of eculizumab treatment. The median patient age was 46 years and median duration of eculizumab treatment was 34 months. Treatment with eculizumab induced rapid inhibition of hemolysis. At 6-month follow-up, LDH decreased to near normal levels in all patients; this effect was maintained until the 36-month follow-up regardless of concurrent AA. Transfusion independence was achieved by 53.3% of patients within the first 6 months of treatment and by 90.9% after 36 months of treatment. The mean number of RBC units transfused was significantly reduced, from 8.5 units during the 6 months prior to initiation of eculizumab to 1.6 units in the first 6 months of treatment, for the total study population; this effect was similar in both PNH/AA and classic PNH. This study demonstrated that eculizumab is beneficial in the management of patients with PNH/AA, similar to classic PNH.